2023
DOI: 10.1371/journal.pntd.0011322
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in patients with paracoccidioidomycosis

Abstract: Introduction In 2020, we reported the first patient with concomitant COVID-19 and paracoccidioidomycosis (PCM). Since then, no other cases have been recorded in the literature. We aim to update information on the occurrence of COVID-19 in patients with PCM followed at a reference center for infectious diseases at Rio de Janeiro, Brazil. Methods We reviewed the medical records from patients diagnosed with PCM who presented with clinical symptoms, radiological findings, and/or laboratory diagnosis of COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Although it has been reported that acute PCM is typically diagnosed within a few weeks of symptoms onset [ 2 ], we observed a considerable delay between the initial clinical symptoms and the confirmation of PCM diagnosis, resulting in postponed treatment that may have contributed to increased severity. This delay is probably due to gaps in providers’ knowledge regarding acute PCM, which is traditionally rare [ 2 , 25 ]. Notably, the high incidence of persistent lymph node involvement among the patients in our study highlights a significant clinical finding that should raise awareness among healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that acute PCM is typically diagnosed within a few weeks of symptoms onset [ 2 ], we observed a considerable delay between the initial clinical symptoms and the confirmation of PCM diagnosis, resulting in postponed treatment that may have contributed to increased severity. This delay is probably due to gaps in providers’ knowledge regarding acute PCM, which is traditionally rare [ 2 , 25 ]. Notably, the high incidence of persistent lymph node involvement among the patients in our study highlights a significant clinical finding that should raise awareness among healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%